Macrolactone glycosides of three lichen acids from Acarospora gobiensis, a lichen of Central Asia - Rezanka, T; Guschina, I A (Phytochemistry, 2001)
The compounds isolated from the extract of Central Asian lichen (Acarospora gobiensis H. Magn.) comprised three new glycosides having 18-hydroxy-dihydroalloprotolichesterinic, 18-hydroxy-neodihydroprotolichesterinic and 18-hydroxy-dihydroprotolichesterinic acids as aglycones and a di- or trisaccharide moiety linked at C-18 and at the carboxylic group. These compounds, called gobienines A-C, were found to be di- or trisacharides forming a macrolactone with the aglycone. The structures were elucidated by using extensive spectroscopic analysis (1D and 2D NMR, MS, IR and ORD) and chemical and enzymatic methods.
Keywords: glykolipidy; Glycosides; Rusko; Lichens; lišejníky; Russia; Glycolipids; glykosidy